Meta-analysis of gene–environment-wide association scans accounting for education level identifies additional loci for refractive error - Qiao Fan (Nature Portfolio, 2016)
This report by the Consortium for Refractive Error and Myopia uses gene-environment-wide interaction study (GEWIS) to identify genetic loci that affect environmental influence in myopia development, and identifies ethnic specific genetic loci that attribute to eye refractive errors.